SOSIALISASI PENERAPAN GOOD MANUFACTURING PRACTICE (GMP) DAN PENGOLAHAN PISANG BAGI SISWA SMK NEGERI I BAWEN - Aldila Sagitaning Putri; Dewi Larasati; Elly Yuniarti Sani (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
One of the expertise programs at SMK Negeri 1 Bawen is the Agribusiness Expertise Program for Processing Agricultural products and Fisheries (APHPP) has one package of expertise, namely Agricultural Product Processing Technology (TPHP). Students of the Agribusiness Expertise Program in Processing Agricultural products and Fisheries (APHPP) SMK Negeri 1 Bawen are prepared to become intermediate skilled workers in the agricultural products processing industry. To accommodate some of the objectives of SMK Negeri 1 Bawen is to equip students with knowledge, skills, and attitudes to be competent in carrying out good ways of production and carrying out the process of making various selected products, it is necessary to add knowledge and skills in terms of Good Manufacturing Practice (GMP) or in the Indonesian of Good Production Methods (CPB) and processing of food products (bananas). Knowledge about the application of GMP to the food industry for the general public and students of SMK Negeri 1 Bawen in particular is still not given to subjects. So it is necessary to socialize the importance of knowledge about the application of GMP and banana processing for students of SmK Negeri Bawen as a provision of knowledge in work and entrepreneurship. To increase / increase knowledge about the application of GMP and banana processing for students  of SmK Negeri Bawen, socialization is carried out by providing the flow of application of GMP and how to make banana flour, banana nuget and banana dodol.  This community service activity aims to provide information to the community, especially for students at SMK Negeri 1 Bawen about the importance of handling post-harvest bananas and how to process them and providing engineering skills for handling fresh bananas and  how to process them. From the results of the devotion, it can be seen that the response from the students of SMK Negeri 1 Bawen is very enthusiastic, this can be seen from the discussions conducted, many questions were given to us, even from the school asking to be given more similar trainings but with different raw materials